2020
DOI: 10.1097/anc.0000000000000669
|View full text |Cite
|
Sign up to set email alerts
|

Giving Voice to Parents in the Development of the Preemie Prep for Parents (P3) Mobile App

Abstract: Background: Parents at risk for preterm birth frequently receive prematurity education when the mother is hospitalized for premature labor. Parental ability to learn and consider the information is limited due to the stress of the hospitalization. A promising approach is dissemination of information to at-risk parents before the birth hospitalization.Purpose: This manuscript describes formative research used to develop smartphone-based prematurity education app for parents at-risk for preterm birth.Methods: St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Although not every expectant mother may be ready to learn about BF when they are separated from their baby, in consideration of their psychological state and mood, as mentioned in the result, those with a high risk of postpartum separation can be identified and educated ahead of time. A smartphone-based prematurity education app named Preemie Prep for Parents (P3) was developed for pregnant women with a high risk of preterm birth and has managed to increase parent knowledge [ 32 , 33 ]. At the Children’s Hospital of Philadelphia, if a woman’s pregnancy is prenatally diagnosed with a fetal anomaly, she will be offered a group prenatal care based on the CenteringPregnancy model [ 34 , 35 ], where she can get support and education on BF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although not every expectant mother may be ready to learn about BF when they are separated from their baby, in consideration of their psychological state and mood, as mentioned in the result, those with a high risk of postpartum separation can be identified and educated ahead of time. A smartphone-based prematurity education app named Preemie Prep for Parents (P3) was developed for pregnant women with a high risk of preterm birth and has managed to increase parent knowledge [ 32 , 33 ]. At the Children’s Hospital of Philadelphia, if a woman’s pregnancy is prenatally diagnosed with a fetal anomaly, she will be offered a group prenatal care based on the CenteringPregnancy model [ 34 , 35 ], where she can get support and education on BF.…”
Section: Discussionmentioning
confidence: 99%
“…Education materials, like paper-based posters or pamphlets, which are inconvenient to carry around, are not actually that practical or efficient [ 47 ]. Provision of educational information through mobile health (mHealth) technology is on the rise, and it has been shown that this promising technology may enhance parents’ capability to understand and apply complex information on BF, even in the event of preterm birth [ 33 , 48 ]. However, if nurses’ preservice education on BF is limited to only a few hours of training, it must be insufficient to provide effective support for the mothers and families [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Health care for newborns has undergone significant transformations (2) as the technology evolved and characterizes a broader universe in care, also including parents in this context, through "mobile health" (m-health) (3,4) . The term mHealth is used to describe any healthcare practice assisted by mobile devices (5) , and it is pointed out as a quick and direct method of distributing information to groups of users (6) . These transformations are in line with the Sustainable Development Goals (SDGs) included in the health agenda through "SDG 3: Good Health and Well-being", which intends that by 2030 there will be no infant and neonatal mortality from preventable causes (7) .…”
Section: Introductionmentioning
confidence: 99%
“… 26 mHealth technology is being touted as a fast and straightforward method of distributing information to targeted groups. 27 28 mHealth technology can provide a versatile and efficient way of informing parents about prematurity. 27 Consultation with physicians during prenatal cycle using mHealth technology can also improve parents’ ability to grasp and apply intricate medical knowledge in the event of early work and delivery.…”
Section: Introductionmentioning
confidence: 99%
“… 27 28 mHealth technology can provide a versatile and efficient way of informing parents about prematurity. 27 Consultation with physicians during prenatal cycle using mHealth technology can also improve parents’ ability to grasp and apply intricate medical knowledge in the event of early work and delivery. 28 Besides, using mHealth applications at the user’s convenience also helps minimise the frequency of unnecessary hospital referrals of stable patients.…”
Section: Introductionmentioning
confidence: 99%